2019
DOI: 10.1103/physreva.100.063610
|View full text |Cite
|
Sign up to set email alerts
|

Faraday patterns generated by Rabi oscillation in a binary Bose-Einstein condensate

Abstract: The interaction between atoms in a two-component Bose-Einstein condensate (BEC) is effectively modulated by the Rabi oscillation. This periodic modulation of the effective interaction is shown to generate Faraday patterns through parametric resonance. We show that there are multiple resonances arising from the density and spin waves in a two-component BEC, and investigate the interplay between the Faraday-pattern formation and the phase separation.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 28 publications
2
20
1
Order By: Relevance
“…(33) by following the method used in Ref. [26]: For a fixed wavenumber, we numerically solve Eq. (33) from t = 0 to T with the initial conditions (S A , S B ) T = (1, 0) T and (0, 1) T , obtaining S 1 (T ) and is the numerically obtained one shown in Fig.…”
Section: Resonant Conditionsmentioning
confidence: 99%
“…(33) by following the method used in Ref. [26]: For a fixed wavenumber, we numerically solve Eq. (33) from t = 0 to T with the initial conditions (S A , S B ) T = (1, 0) T and (0, 1) T , obtaining S 1 (T ) and is the numerically obtained one shown in Fig.…”
Section: Resonant Conditionsmentioning
confidence: 99%
“…In a recent paper [28], the authors found that the Faraday patterns can also be excited from a quench of the phase of the Rabi coupling without any modulation of the system's parameters. The effective modulation of interaction can be realized when the interaction coefficients satisfy g 2 12 = g 11 g 22 and the average populations of two hyperfine states of the spinor BEC experience Rabi oscillation.…”
Section: Introductionmentioning
confidence: 99%
“…However, according to the simulation in Ref. [28], it takes a long time for the Faraday patterns to emerge and in a practical experiment, the tuning range of |g 2 12 − g 11 g 22 | is limited. Motivated by Ref.…”
Section: Introductionmentioning
confidence: 99%
“…The phenomenon of parametric resonances (PRs) is ubiquitious in nature and is a widely examined fundamental physical property. Today, PRs are one of the outstanding features observed in Bose-Einstein condensates (BECs) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] where resonances are usually the result of modulating one of the system parameters such as the scattering length [11,[19][20][21][22]. They are also generated by external means such as a time-dependent trapping geometry [11], laser stirring [2], and laser-intensity modulation [1].…”
Section: Introductionmentioning
confidence: 99%